The impact of urban shrinkage on land prices and its spatial spillover effects - CHEN Shuxing, FU Wenqiang, WU Kang (Ziyuan Kexue, 2024)
[Objective] In recent years, the phenomenon of urban shrinkage has become increasingly prominent in China, and it is of great significance to accurately identify this phenomenon and its influence mechanism on land prices, which may help in guiding the construction of new urbanization and coordinated regional development. [Methods] This study used the panel data of Chinese cities from 2011 to 2021 to establish a spatial Durbin model through threshold regression and spatial autocorrelation test and to explore the impact of urban shrinkage on urban land prices. [Results] (1) After controlling for the fixed effect of province and time, the regression results show that the urban shrinkage is negatively correlated with land price, indicating that the city with urban shrinkage was called the city without urban shrinkage, and the land price is lower. (2) The regression analysis divides the sample into three regions and finds that the negative impact of urban shrinkage of central and western regions on land price is more significant, while the shrinkage of eastern cities is not significant, which indicates that the impact of urban shrinkage in different regions on land price is heterogeneous. (3) Taking per capita carbon emissions as the threshold variable, the results show that with the increase of per capita carbon emissions, there is a structural break point in the impact of urban shrinkage on land price, especially after crossing the threshold. (4) The results of the spatial econometric model show that due to the significant spatial spillover effect of urban shrinkage, the shrinkage of one city causes the rise of land prices in surrounding cities. This suggests that there is a spatial correlation between urban shrinkage and impact on nearby cities. [Conclusion] Urban shrinkage is an unavoidable problem in the process of urbanization in the new stage of development. Therefore, it is of great significance to adopt differentiated shrinkage strategies to guide the urban economic development of various regions and maintain stable and controllable land prices. The results of this study provide important policy implications for the government to coordinate regional development, strengthen environmental protection, and optimize the allocation of land resources.